Construction of MUC2 promoter-type periodontitis DNA vaccine candidate plasmid and preliminary exploration of the effect of Lactobacillus rhamnosus on its expression - Bin Chen; Rujia Wang; Yongfeng Zhao; Yufei Qian; Guanghang Wang; Qin Fan; Guohui Bai (PLoS ONE, 2026)
Background Conventional cytomegalovirus (CMV) promoter-type periodontitis vaccines can offer protection against periodontitis; however, their antigen genes can be widely expressed in the body, resulting in significant toxic effects. This study aimed to modify the CMV promoter for targeted expression of antigen genes, investigate appropriate methods for regulating its expression, and explore its regulatory mechanism. Methods We searched for the MUC2 promoter sequence in the UCSC database, replaced the original broad-spectrum CMV promoter type pVAX1-CMV pro - HA2-fimA periodontitis DNA vaccine candidate with the MUC2 promoter sequence, and constructed the pVAX1-MUC2 pro -HA2-fimA-EGFP periodontitis DNA vaccine. We assessed the intestinal-specific expression ability of the MUC2 promoter-type periodontitis DNA vaccine candidate by transfecting different tissue cells. Subsequently, various concentrations of Lactobacillus rhamnosus supernatant were used to stimulate intestinal tissue cells transfected with the MUC2pro periodontitis DNA vaccine. Real-time quantitative polymerase chain reaction (RT-qPCR) and Western blotting (WB) assays were used to confirm the regulatory effect of Lactobacillus rhamnosus supernatant. After transfection, TGF-β pathway inhibitors were used to target intestinal tissue cells cultured with Lactobacillus rhamnosus supernatant. RT-qPCR and WB assays were used to assess the impact of TGF-β inhibitors on the regulatory effect of Lactobacillus rhamnosus supernatant. All statistical analyses were performed using SPSS 29.0, with one-way ANOVA for multiple group comparisons and LSD/Tamhane’s T2 for post-hoc tests; P < 0.05 was considered statistically significant. Results After transfection with the MUC2 promoter-type periodontitis vaccine plasmid, green fluorescence was exclusively detected in LS-174T cells, while it was absent in LX-2, BEAS-2B, and U251 cells. Compared with the control group of LS 174T cells transfected without SN, the 2% SN group exhibited no enhancement of vaccine antigen expression ( P > 0.05). The 4% SN group enhanced vaccine antigen expression ( P < 0.05), while the 8% SN group significantly promoted vaccine antigen expression ( P < 0.01). Compared with the control group without SN, the PFD group exhibited no inhibitory effect on vaccine antigen expression in transfected LS-174T cells ( P > 0.05). Compared with the 8% SN group, the expression of vaccine antigens in LS-174T cells transfected with the 8% SN + PFD group was significantly inhibited ( P < 0.05). Conclusions Periodontitis DNA vaccine candidate plasmid pVAX1-MUC2 pro - HA2-fimA-EGFP was engineered for intestinal tissue-specific expression. Additionally, an appropriate concentration of Lactobacillus rhamnosus supernatant enhances MUC2 promoter-type periodontitis DNA vaccine candidate expression, which may be associated with TGF-β pathway regulation. EGFP was used as a surrogate marker for HA2/fimA expression in this study, and P2A cleavage efficiency was assumed but not validated, representing an indirect readout of antigen expression.